Análise da resistência antimicrobiana em cepas de Pseudomonas aeruginosa isoladas em Unidades de Tratamento Intensivo em Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
Introduction: Pseudomonas aeruginosa resistant to multiple antibiotics (MDR , multi-drugresistance and PDR , pan-drug-resistance ) is a frequent etiologic agent of nosocomial infections, mainly affecting immunocompromised patients, such as those admitted to the Intensive Care Unit (ICU). Objectives: (1) Detect P. aeruginosa resistant to multiple antimicrobials in patients, professionals and hospital environment; (2) Identify genetic factors that confer antibiotic resistance such as integrons, gene cassettes and genes encoding enzymes β-lactamases; and (3) Detect clonal groups among isolates MDR/PDR. Methods: Samples were collected samples from patients, professionals and structures in ICUs of Hospitals 28 de Agosto (HPS28), Francisca Mendes (HUFM) e João Lúcio Pereira Machado (HPSJL), which were isolated and identified strains of P. aeruginosa by classical and molecular microbiological methods (amplification and sequencing of the 16S rRNA gene); The antimicrobial resistance profile was determined by disk diffusion technique; The research groups was determined by clonal genetic similarity among isolates MDR/PDR by PFGE; The detection of genes that encode resistance (integrons, gene cassettes and β-lactamases enzymes) was performed by PCR and confirmed by RFLP and/or genetic sequencing. Results: The phenotypes MDR and PDR were detected, respectively, 13.3 % and 1.2 % of the isolates. In 32 (38.5%) were detected class integrons 1. Of these, three (3.6%) were also positive for integrons class intengrons 2. The presence of the isolates showed statistical correlation (P<0.05) with significant phenotypic resistance to the tested drugs. A high frequency of integrons contained no genetic cassette or carried only genes that encode resistance to aminoglycosides streptomycin and spectinomycin and trimethoprim. The β- lactamase showed the production of enzyme KPC -2 study (66,7%), VIM (8.3%) and OXA - 50 (100%) P. aeruginosa isolates MDR/PDR. Two clonal groups were detected among MDR/PDR isolates, indicating clonal intra and inter-hospital. Conclusion: The isolation of P. aeruginosa from hospitals studied shows that these pathogens, which can cause severe nosocomial infections, in particular MDR and PDR strains are spreading in a hospital environment. Moreover, it appears that the presence of genetic elements such as integrons, gene cassettes and genes encoding β-lactamases are correlated to the resistance fenótops these isolates and therefore potential genetic mechanisms that confer antimicrobial resistance. Nevertheless, further studies are needed to assess the contribution of other molecular mechanisms and the selective pressure exerted by antimicrobial agents that contribute to the development of these phenotypes.
Keywords: Resistência antimicrobiana; Cassetes gênicos; Antimicrobianos; Infecções nosocomiais; CIÊNCIAS BIOLÓGICAS